2000
DOI: 10.1007/s002039900131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an l -dopa decarboxylase gene from Sorangium cellulosum So ce90

Abstract: During a screening program intended to identify genes encoding enzymes typical for secondary metabolism in Sorangium cellulosum So ce90, an aromatic amino acid decarboxylase gene (ddc) was detected. Expression of ddc in Escherichia coli and subsequent enzyme assays with cell-free extracts confirmed the proposed function derived from amino acid sequence comparisons. In contrast to other aromatic amino acid decarboxylases of eukaryotic origin, the S. cellulosum Ddc converted only L-dihydroxy phenylalanine. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In contrast to the theory mentioned in the last paragraph, amino acid sequence analyses revealed top scores of DDC from S. cellulosum So ce56 grouping with plant and animal but not with bacterial group-II aromatic amino acid decarboxylases. Phylogenetic analysis of the DDC amino acid sequences suggests a closer link to the plant branch of AADs as well, which indicates that DDC in S. cellulosum is the result of a horizontal gene transfer event (Mü ller et al, 2000). Hybridization studies with other myxobacteria and data bank searches show that AADs are not commonly found in bacteria.…”
Section: Chalcone Synthases (Chss) and Pkss Are Common In Plants And mentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to the theory mentioned in the last paragraph, amino acid sequence analyses revealed top scores of DDC from S. cellulosum So ce56 grouping with plant and animal but not with bacterial group-II aromatic amino acid decarboxylases. Phylogenetic analysis of the DDC amino acid sequences suggests a closer link to the plant branch of AADs as well, which indicates that DDC in S. cellulosum is the result of a horizontal gene transfer event (Mü ller et al, 2000). Hybridization studies with other myxobacteria and data bank searches show that AADs are not commonly found in bacteria.…”
Section: Chalcone Synthases (Chss) and Pkss Are Common In Plants And mentioning
confidence: 98%
“…Thus, one would expect a DDC of prokaryotic origin to show the highest similarities to group II AADs of prokaryotic origin, despite possible differences in substrate specificity (Mü ller et al, 2000).…”
Section: Chalcone Synthases (Chss) and Pkss Are Common In Plants And mentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with their function in Salmonella infection, the two latter proteins might be involved in the B. pseudomallei-induced apoptosis, cell fusion and actin-associated membrane protrusion, the phenotypes recently reported (8). No putative homologues of other SPI-1 TTS effectors SipA, SopA, SopB, SptP and AvrA (6) were found in the B. pseudomallei genome. It is possible that genes encoding additional TTS-delivered effectors are scattered throughout the B. pseudomallei genome and await molecular characterization.…”
Section: Measurement Of Genome Evolution In Mrsamentioning
confidence: 98%
“…Early reports (5,6) characterizing ISR sequences found a total of 10 different ISR types from three MRSA strains (H11, ATCC 33952 and D46). Whole genome sequence analysis from five other strains (N315, 252, Mu50, 8325 and COL) shown in Table 1a shows that (i) each of the ISR types found in the five whole genomes unambiguously matched one of the ISR types found earlier in strains H11, ATCC 33952 and D46 (5,6) (no additional ISR types were found), (ii) some ISR types were present in some and absent in other strains (e.g. rrnA1 was only present in strain COL), (iii) some ISR types were present in different copy numbers in different strains (e.g.…”
Section: Variation In the Type Of Isr Found In Mrsa Strainsmentioning
confidence: 99%